Preparation method and application of swelling-inhibiting dual-network membrane
By employing a dual-network structure of CMPSF and SPEEK, combined with TMEDA crosslinking and gradient cooling processes, the problems of uncontrolled swelling and insufficient mechanical properties of alkaline zinc-iron flow battery separators were solved, achieving high-efficiency ion conduction and anti-zinc dendrite capabilities, thus extending battery life.
Patent Information
- Application Number
- CN202511594073.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-03
- Publication Date
- 2026-01-27
AI Technical Summary
Existing alkaline zinc-iron flow battery separators suffer from uncontrolled swelling and incompatibility between ion conduction and mechanical properties in a strongly alkaline environment, leading to zinc dendrites piercing the separator and causing battery short-circuit failure.
Using chloromethylated polysulfone (CMPSF) and sulfonated polyether ether ketone (SPEEK) as the matrix, a dual network structure of covalent cross-linking + hydrogen bonding is formed by precise cross-linking of tetramethylethylenediamine (TMEDA) in a weakly alkaline environment and combined with a gradient cooling process. This optimizes the microphase structure and forms a composite structure of rigid framework and flexible channels.
It achieves low swelling, high ionic conductivity and excellent mechanical properties in a strongly alkaline environment, effectively suppresses zinc dendrite puncture, extends battery life, and improves energy efficiency and capacity retention.
Smart Images

Figure CN121416539A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flow battery separator technology, specifically to a method for preparing a swelling-suppressing dual-network membrane and its application. Background Technology
[0002] Alkaline zinc-iron flow batteries (AZIFBs) have become a key candidate technology for large-scale, long-term energy storage due to their abundant resources and long cycle life. However, the core component, the separator, faces prominent challenges in alkaline electrolytes, such as uncontrolled swelling and incompatibility between ion conduction and mechanical properties. The flexible polymer chains of commonly used separators are prone to relative sliding, and the hydrophilic groups introduced to improve ion conductivity adsorb a large number of water molecules into the gaps between polymer networks, causing excessive swelling. Swelling not only causes deformation of ion channels and an imbalance between ion selectivity and conductivity (leading to irreversible capacity decay), but also weakens the interaction forces between polymer chains, causing a sharp decline in the mechanical properties of the separator. It is difficult to suppress the vertical growth of dendrites generated during the charging and discharging of the zinc anode. Under high areal capacity or high current density, the local stress caused by the accumulation of zinc dendrites can easily puncture the separator, causing the battery to short-circuit and fail.
[0003] Existing membrane modification strategies (such as composite membranes of "non-fluorine ion exchange membrane + single-sided sprayed porous layer" for acidic vanadium batteries, and excessively dense covalent cross-linked membranes) either lack stability in alkaline environments due to their suitability for acidic systems, or sacrifice ion conduction efficiency and membrane toughness due to excessive restriction of chain segment movement. None of these strategies can meet the synergistic requirements of AZIFB for "low swelling, high ion conduction, strong mechanical properties, and resistance to zinc dendrites". Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a swelling-inhibiting dual-network membrane and its application. By precisely controlling the density of the covalent cross-linked network and directionally optimizing the blended microphase structure, it simultaneously achieves a synergistic improvement in "swelling inhibition, efficient ion conduction, excellent mechanical properties, and resistance to zinc dendrites" under a strongly alkaline environment.
[0005] In one aspect of the invention, a method for preparing a swelling-suppressing dual-network membrane is provided. According to an embodiment of the invention, the method includes the following steps:
[0006] (1) Chloromethylated polysulfone (CMPSF) and tetramethylethylenediamine (TMEDA) were placed in NaOH solution for pre-crosslinking to obtain a crosslinked chloromethylated polysulfone solution;
[0007] (2) Mix the cross-linked chloromethylated polysulfone solution with the sulfonated polyether ether ketone (SPEEK) solution, stir at 60-80℃ for 2-4h, then cool to 40-50℃ at a rate of 5-10℃ / h, and stir at a constant temperature for 8-12h to obtain the casting solution.
[0008] The gradient cooling process allows the molecular chains of SPEEK and cross-linked CMPSF to be arranged more orderly, and the microdomain size is uniformly controlled within 10-50 nm, which not only inhibits network swelling but also ensures rapid ion transport in the "continuous channel".
[0009] (3) Dry the casting solution to obtain the swelling-inhibiting double network membrane.
[0010] In addition, the method for preparing a swelling-inhibiting dual-network membrane according to the above embodiments of the present invention may also have the following additional technical features:
[0011] In some embodiments of the present invention, in step (1), the molar ratio of the chloromethylated polysulfone and tetramethylethylenediamine is 1:1-1:3; and the concentration of the NaOH solution is 0.05-0.2 mol / L.
[0012] In some embodiments of the present invention, in step (1), the pre-crosslinking temperature is 50-60°C and the time is 20-40 min.
[0013] Step (1) involves “pretreatment in a weakly alkaline environment” to enable the chloromethyl group of CMPSF to react efficiently with the amino group of TMEDA. The resulting quaternary ammonium group is adapted to the alkaline electrolyte in advance to avoid the degradation of cross-linking bonds caused by alkaline corrosion in the later stage. At the same time, by adjusting the molar ratio of TMEDA to CMPSF, the density of covalent cross-linking network can be precisely controlled to balance “swelling inhibition” and “ion conduction”.
[0014] In some embodiments of the present invention, in step (2), the mass ratio of the crosslinked chloromethylated polysulfone solution to the sulfonated polyether ether ketone solution is 1:1-1:9.
[0015] The cross-linked chloromethylated polysulfone component imparts a robust three-dimensional structure to the membrane, while the sulfonated polyether ether ketone component provides highly efficient ion conduction. The two components form a stable "rigid framework-flexible channel" composite structure through microscopic phase separation, which is the fundamental reason for achieving low swelling and high conductivity in high-performance anion exchange membranes.
[0016] In some embodiments of the present invention, in step (2), the solvent of the sulfonated polyether ether ketone solution is a mixed solvent of dimethylacetamide and water, the concentration of the sulfonated polyether ether ketone solution is 0.6-1.0 g / mL, and the amount of chloromethylated polysulfone added is 10%-35% of the mass of the sulfonated polyether ether ketone.
[0017] In some embodiments of the present invention, the volume ratio of dimethylacetamide to water is (95-85):(5-15). The introduction of water is crucial, as it induces pre-aggregation of hydrophilic sulfonic acid groups on the SPEEK chain. Simultaneously, hydrophobic quaternary ammonium groups generated from TMEDA are distributed on the crosslinked CMPSF segments. This hydrophilic / hydrophobic difference promotes microphase separation, forming an ideal nanostructure with continuous ion clusters as channels. For ion transport: these pre-formed continuous ion clusters provide a dedicated pathway for the efficient transport of hydroxide ions (OH⁻), ensuring the ionic conductivity of the membrane. For swelling control: because ion transport is confined within these nanoscale, structurally stable ion channels, disordered permeation and adsorption of water throughout the polymer matrix are avoided. Therefore, while achieving efficient ion conduction, the macroscopic swelling and water absorption rate of the entire membrane are effectively controlled.
[0018] In some embodiments of the present invention, in step (3), the drying is carried out in a vacuum environment, the drying temperature is 60-70°C, and the time is 16-24h.
[0019] In another aspect of the invention, the invention proposes a swelling-inhibiting dual-network membrane prepared according to the preparation method described above.
[0020] In another aspect, the present invention provides an alkaline zinc-iron flow battery. According to an embodiment of the invention, the separator is the aforementioned swelling-inhibiting double-network membrane. The positive electrode electrolyte composition of this battery is 0.4 mol / L. -1 Fe(CN)6 4- and 4 mo / L NaOH; the composition of the negative electrode electrolyte is 0.4 mol / L. Zn(OH)4 2- and 4mol / L NaOH; the volume of the positive and negative electrode electrolytes is 80 mL each; both the positive and negative electrodes are porous carbon felt electrodes, and the graphite plate is used as the current collector.
[0021] Compared with the prior art, the beneficial effects of the present invention are:
[0022] (1) The present invention uses chloromethylated polysulfone (CMPSF) and sulfonated polyether ether ketone (SPEEK) as the matrix, and precisely crosslinks them with tetramethylethylenediamine (TMEDA) in a weakly alkaline environment. The structure of the blended microphase is optimized by mixing solvents and gradient cooling process to form a dual network of "covalent crosslinking + hydrogen bonding".
[0023] (2) Low swelling in a strongly alkaline environment: Through "alkaline pre-crosslinking" and "precise control of the TMEDA / CMPSF molar ratio", CMPSF has a rigid framework and excellent chemical stability; its chloromethyl (-CH2Cl) can participate in the crosslinking reaction to form a dense network structure. TMEDA is a strongly alkaline ligand that can effectively promote the quaternization reaction; at the same time, it can control the crosslinking density: when the TMEDA / CMPSF molar ratio is appropriate, a uniform and controllable crosslinking network can be formed, reducing the gaps between molecules and making it difficult for water molecules to penetrate; it also reduces the mobility of polymer chains and limits volume expansion. The swelling rate of the membrane after soaking in 4 mol / L NaOH electrolyte for 24 h is ≤6.5%, which is much lower than that of commercial membranes (such as Nafion membranes) and unmodified blended membranes, thus avoiding ion channel deformation and mechanical property degradation from the source.
[0024] (3) The present invention achieves an ionic conductivity of ≥10mS / cm in the membrane by using a “continuous ion cluster channel” induced by a mixed solvent; at the same time, the selectivity of ferrocyanide and ferricyanide ensures the energy efficiency and capacity of the alkaline zinc-iron flow battery.
[0025] (4) Excellent mechanical properties and resistance to zinc dendrites: The "dual network structure plus gradient cooling oriented micro-domains" endows the separator with the characteristics of "rigidity and flexibility". The tensile strength in the fully hydrated state is ≥38 MPa. At a high areal capacity of 240 mAh / cm² and a current density of 100mA / cm², the energy efficiency of the AZIFB assembled based on this separator is ≥85% after 800 h of cycling, effectively suppressing zinc dendrite puncture and significantly extending the battery life. Alkaline system-specific adaptability: The directional optimization of alkaline pretreatment and blending system makes the separator chemically stable in strongly alkaline electrolytes, solving the problem of easy degradation and sudden performance drop of acidic system separators (such as the "non-fluorine membrane + porous layer" composite membrane for vanadium batteries) in alkaline environments. It is specially customized for the strongly alkaline conditions of AZIFB. Attached Figure Description
[0026] Figure 1 The 1H NMR spectrum of sulfonated polyether ether ketone (SPEEK) in Example 1 of this invention;
[0027] Figure 2 The 1H NMR spectrum of chloromethylated polysulfone (CMPSF) in Example 1 of this invention;
[0028] Figure 3 XPS spectra of H-DN-25 and PBM in Embodiment 1 of the present invention;
[0029] Figure 4 The diagram shows the ionic conductivity of the swelling-inhibiting double-network membrane H-DN-x prepared in Examples 1-3 of this invention.
[0030] Figure 5 The tensile strength diagrams are of the swelling-inhibiting double-network membrane H-DN-x prepared in Examples 1-3 of this invention.
[0031] Figure 6 The swelling rate and water absorption rate test graphs of the diaphragms prepared in Example 1 and Comparative Examples 1-3 of this invention are shown.
[0032] Figure 7 For the batteries assembled with the separators of H-DN-25 in Application Example 1 and Comparative Example 1 of this invention, the current density is 40-240 mA / cm². 2 Ratio performance diagram;
[0033] Figure 8 The battery assembled using the H-DN-25 separator in Application Example 1 of this invention, and the separators in Comparative Examples 1-3, achieves a speed of 80 mA / cm². 2 Current density and 100 mAh / cm 2 Battery cycle performance diagram at areal capacity;
[0034] Figure 9 The battery assembled using the H-DN-25 separator in Application Example 1 and Comparative Example 3 of this invention achieves a speed of 72 mA / cm². 2 Current density and 240 mAh / cm 2 Battery cycle performance diagram under areal capacity. Detailed Implementation
[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0036] Example 1
[0037] A method for preparing a swelling-inhibiting dual-network membrane includes the following steps:
[0038] (1) Preparation of sulfonated polyether ether ketone (SPEEK)
[0039] Weigh 4 g of polyetheretherketone (PEEK) powder and measure 80 mL of concentrated sulfuric acid using a graduated cylinder. Add 80 mL of concentrated sulfuric acid to a flask, heat to 60 °C in a water bath, pour in the PEEK, and maintain the sulfonation reaction for 5 hours. After the reaction is complete, pour the solution into ice water to terminate the sulfonation reaction, yielding a white SPEEK product. Stir overnight, and when the pH of the washing solution is close to neutral, the washing is complete. Finally, place the SPEEK in a vacuum oven and dry for 12 hours.
[0040] SPEEK 1 H NMR characterization was used to determine whether PEEK was successfully grafted with sulfonic acid groups. Figure 1 Characterization results showed that the hydrogen chemical position on the ortho-benzene ring of the sulfonate group shifted to a higher field, proving that sulfonic acid groups were successfully grafted onto the PEEK backbone, and SPEEK was successfully synthesized.
[0041] (2) Preparation of chloromethylated polysulfone (CMPSF)
[0042] Weigh 4 g of polysulfone (PSF) into a flask and measure 60 mL of chloroform using a graduated cylinder. Add 60 mL of chloroform to the flask, then slowly add 0.25 mL of chloromethyl ether. Heat the mixture to 55°C in a water bath and react under a nitrogen atmosphere for 48 hours. Pour in excess ethanol, stir, filter, and dry to obtain CMPSF.
[0043] Chloromethylated polysulfone 1 H NMR characterization was used to determine whether chloromethylation was successfully performed on the polysulfone. Figure 2 The characterization results showed a new peak at 4.64 ppm, proving that polysulfone was successfully chloromethylated.
[0044] (3) Preparation of cross-linked CMPSF solution
[0045] Take chloromethylated polysulfone (CMPSF) and tetramethylethylenediamine (TMEDA), mix them in a molar ratio of 1:2, and add 0.1 mol / L... NaOH solution was used for pre-crosslinking at 55℃ for 30 min to obtain crosslinked CMPSF solution.
[0046] (4) Preparation of a swelling-inhibiting double-network membrane
[0047] The cross-linked CMPSF solution and SPEEK solution (a mixture of DMAc and water in a volume ratio of 95:5, with a SPEEK concentration of 0.8 g / mL) were mixed at a mass ratio of 1:3 and stirred at 80 °C for 3 h. The mixture was then cooled to 40 °C at a rate of 5 °C / h and stirred at a constant temperature for 12 h to obtain the casting solution. The solution was dried under vacuum at 65 °C for 20 h to obtain a swelling-inhibiting double-network membrane, denoted as H-DN-25.
[0048] Example 2
[0049] A method for preparing a swelling-inhibiting dual-network membrane, which differs from Example 1 only in that: in the mixing step (4), the crosslinked CMPSF solution and SPEEK solution are mixed at a mass ratio of 1:2, and the final prepared dual-network membrane is denoted as H-DN-35.
[0050] Example 3
[0051] A method for preparing a swelling-inhibiting dual-network membrane differs from Example 1 only in that: in step (4), the crosslinked CMPSF solution and SPEEK solution are mixed at a mass ratio of 1:9, and the final prepared dual-network membrane is denoted as H-DN-10.
[0052] The performance of H-DN-x prepared in Examples 1-3 was tested:
[0053] (1) XPS test on H-DN-25 membrane
[0054] like Figure 3 As shown, the new peak at 402.1 eV for N 1s corresponds to the quaternary ammonium group (-N⁺(CH3)). 2- The characteristic peak of the crosslinking agent can prove the sufficiency of the crosslinking reaction by its intensity and shape. If the peak is broadened or the intensity is insufficient, it indicates that the quaternary ammonium groups are unevenly distributed or the degree of crosslinking is insufficient. This also provides a characterization basis for adjusting the amount of crosslinking agent in the future.
[0055] (2) Ionic conductivity of H-DN-x.
[0056] To evaluate the ion conduction performance of the H-DN-x dual-network membrane, electrochemical impedance spectroscopy (EIS) was performed. Figure 4 As shown, in this dual-network membrane system, the internal resistance of the membrane exhibits a significant upward trend as the proportion of cross-linked chloromethyl polysulfone (CMPSF) within the membrane gradually increases. This is because the cross-linked CMPSF constructs a denser covalent cross-linked network structure within the membrane. While this structure helps suppress membrane swelling and enhances mechanical properties, it also restricts ion transport channels within the membrane, increasing the resistance encountered during ion transport and consequently leading to a continuous increase in the membrane's internal resistance, ultimately negatively impacting the membrane's ion conductivity.
[0057] (3) Tensile strength of H-DN-x.
[0058] The tensile strength and elongation at break of the H-DN-x double-network membrane were tested using an electronic universal testing machine at a tensile speed of 1 mm / min to evaluate its mechanical properties. The test results are as follows: Figure 5 As shown, the results indicate that the tensile strength of the hybrid dual-network membrane increases with the increase of the proportion of chloromethylated polysulfone, which gives the membrane a good advantage in alkaline zinc-iron flow batteries. It can effectively resist zinc dendrites piercing the membrane and improve the cycle life of the battery.
[0059] Comparative Example 1
[0060] A method for preparing a diaphragm includes the following steps:
[0061] Chloromethylated polysulfone and sulfonated polyether ether ketone were dissolved in N,N-dimethylacetamide and stirred at room temperature for 12 hours to obtain a casting solution with a concentration of 0.8 g / mL. The mass ratio of chloromethylated polysulfone to sulfonated polyether ether ketone was 1:3. The solution was then dried overnight in a vacuum oven. The glass plate was then completely immersed in water to obtain a blended membrane, denoted as PBM.
[0062] Comparative Example 2
[0063] A method for preparing a diaphragm includes the following steps:
[0064] The sulfonated polyether ether ketone prepared in Example 1 was dissolved in N,N-dimethylacetamide to prepare a sulfonated polyether ether ketone casting solution of 0.8 g / mL, and the SPEEK membrane was obtained by solution casting.
[0065] Comparative Example 3
[0066] A diaphragm, which is the commercially available Nafion 212 membrane.
[0067] The swelling rate and water absorption rate of the membranes prepared in Example 1 and Comparative Examples 1-3 were tested:
[0068] The sample was immersed in deionized water for 48 hours, then removed and dried with filter paper. Its mass and dimensions after water absorption were then measured. The water absorption rate was obtained by calculating the percentage change in mass before and after water absorption; the swelling rate was determined by measuring and comparing the dimensional changes of the sample before and after water absorption. Figure 6 As shown, the low swelling rate of the dual-network membrane in Example 1 is due to the cross-linked structure forming a rigid network that restricts the movement of polymer chains, thereby effectively improving the dimensional stability of the membrane.
[0069] Application Example 1
[0070] The positive electrode electrolyte composition of the alkaline zinc-iron flow battery is 0.4 mol / L. Fe(CN)6 4- and 4 mol / L NaOH; Negative electrode electrolyte composition: 0.4 mol / L Zn(OH)4 2- and 4mol / L NaOH; 80 mL of electrolyte for both positive and negative electrodes; porous carbon felt electrodes for both positive and negative electrodes; graphite plate as current collector; and membranes from Examples 1-3 and Comparative Examples 1-3 as diaphragms, respectively.
[0071] The single cell is assembled in the following order: steel plate, PTFE plate, copper sheet, graphite collector, and positive electrode 2×2cm. 2 Carbon felt, diaphragm prepared according to the examples or comparative examples, negative electrode 2×2cm 2Carbon felt, graphite sheets, copper sheets, PTFE sheets, steel sheets.
[0072] Alkaline zinc-iron flow battery test conditions: effective electrode area is 4 cm². 2 The battery uses a constant current charge / discharge mode, at 80 mA / cm². 2 Under the given current density, it was charged for 1.25 hours, then the voltage was cut off and discharged to 0.1V; at 240mAh / cm²... 2 It can be charged for 6.67 hours with its ultra-high areal capacity, and then the voltage is cut off when it is discharged to 0.1V.
[0073] The rate performance and cycle stability of H-DN-25 prepared in Example 1 were tested first, and the results are as follows:
[0074] (1) The variable current performance of the H-DN-25 dual-network membrane in an alkaline zinc-iron flow battery was tested, and the experimental results are as follows: Figure 7 As shown, a current density range of 40-240 mA / cm² is selected, covering the practical application scenarios of alkaline zinc-iron flow batteries. Low current density (40-80 mA / cm²) corresponds to the stable discharge requirements for long-term energy storage, while high current density (160-240 mA / cm²) corresponds to the high power requirements for emergency power supply. Figure 7 The results show that the coulombic efficiency and energy efficiency of the H-DN-25 membrane are higher than those of the commercially available Nafion 212, demonstrating its adaptability to the power requirements of various energy storage scenarios. This is because the dual-network membrane retains the abundant hydrogen bond network within the SPEEK, providing rapid ion transport and thus exhibiting lower ion transport internal resistance.
[0075] (2) The cycling stability of H-DN-25 in an alkaline zinc-iron flow battery was tested. Cycling stability directly reflects the stability of the separator under long-term alkaline conditions. At 80 mA / cm²... 2 Current density and 100 mAh / cm 2 It operated for over 700 hours at its current capacity. Subsequently, at 240 mAh / cm²... 2 It operates for over 800 hours with an average EE of ~88.87% at ultra-large areal capacity. This is because the rigidly cross-linked polysulfone skeleton within H-DN-25 locks the chain segment movement of sulfonated polyether ether ketone, reducing membrane swelling and improving the membrane's mechanical strength, which is sufficient to resist vertically growing dendrite puncture.
[0076] like Figure 8-9 As shown, the diaphragms of Comparative Examples 1-3 were subjected to an energy density of 80 mA / cm. 2 Current density and 100 mAh / cm 2 Cyclic testing was conducted at the areal capacity: in Comparative Example 1, the diaphragm was tested at 80 mA / cm². 2Current density and 100 mAh / cm 2 After operating at 83% energy efficiency for 164 hours at its areal capacity, the membrane was punctured by dendrites. The flow battery assembled with the membrane in Comparative Example 2 operated at 80 mA / cm². 2 Current density and 100 mAh / cm 2 After operating at 86% energy efficiency (EE) for 80 hours at its areal capacity, the membrane was punctured by dendrites. Subsequently, at 240 mAh / cm²... 2 During cycle testing, after 120 hours of operation at 88.87% EE, the separator was punctured by dendrites. The flow cell assembled with the separator in Comparative Example 3 operated at 80 mA / cm². 2 Current density and 100 mAh / cm 2 Cyclic testing was conducted at its areal capacity, and after 205 hours of operation with 80% energy efficiency, the membrane was punctured by dendrites. Subsequently, at 240 mAh / cm²... 2 During the cycle test, the membrane was punctured by dendrites after running for more than 200 hours at 78% EE.
[0077] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the present invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A method for preparing a swelling-inhibiting dual-network membrane, characterized in that, Includes the following steps: (1) Chloromethylated polysulfone and tetramethylethylenediamine were placed in NaOH solution for pre-crosslinking to obtain a crosslinked chloromethylated polysulfone solution; (2) Mix the cross-linked chloromethylated polysulfone solution with the sulfonated polyether ether ketone solution, stir at 60-80℃ for 2-4h, then cool down to 40-50℃ at a rate of 5-10℃ / h, and stir at a constant temperature for 8-12h to obtain the casting solution. (3) Dry the casting solution to obtain the swelling-inhibiting double network membrane.
2. The method for preparing a swelling-inhibiting dual-network membrane according to claim 1, characterized in that: In step (1), the molar ratio of the chloromethylated polysulfone and tetramethylethylenediamine is 1:1-1:3; the concentration of the NaOH solution is 0.05-0.2 mol / L.
3. The method for preparing a swelling-inhibiting dual-network membrane according to claim 1, characterized in that: In step (1), the pre-crosslinking temperature is 50-60℃ and the time is 20-40min.
4. The method for preparing a swelling-inhibiting dual-network membrane according to claim 1, characterized in that: In step (2), the mass ratio of the cross-linked chloromethylated polysulfone solution to the sulfonated polyether ether ketone solution is 1:1-1.
5. The method for preparing a swelling-inhibiting dual-network membrane according to claim 1, characterized in that: In step (2), the solvent of the sulfonated polyether ether ketone solution is a mixed solvent of dimethylacetamide and water, and the concentration of the sulfonated polyether ether ketone solution is 0.6-1.0 g / mL.
6. The method for preparing a swelling-inhibiting dual-network membrane according to claim 5, characterized in that: The volume ratio of dimethylacetamide to water is (95-85):(5-15).
7. The method for preparing a swelling-inhibiting dual-network membrane according to claim 1 and its application, characterized in that: In step (3), the drying is carried out in a vacuum environment at a temperature of 60-70°C for 16-24 hours.
8. A swelling-inhibiting double-network membrane prepared by the preparation method according to any one of claims 1-7.
9. An alkaline zinc-iron flow battery, comprising a separator, characterized in that: The diaphragm is the swelling-inhibiting double-network membrane as described in claim 8.